When the West Meets the East: Cultural Clash and Its Impacts on Anomie in a Sample of Chinese Adolescents. Issue 10 (3rd October 2019) - Zhao, Ruohui; Zhang, Hongwei; Zhao, Jihong Solomon; Wang, Xinting
ABSTRACT: Criminological studies conducted in China have highlighted the important role of Chinese culture and anomie theory in explaining crime patterns and delinquency among adolescents. None of the studies, however, have empirically tested the relationship between cultural attachment and anomie. The purpose of this study is to examine the influence of ethnic identity associated with cultural attachment on anomie in the Chinese social setting. Specifically, the effects of both attachment to conventional Chinese culture and attachment to Western popular culture (WPC) were examined; the interaction between the two may shed some important light on how culture and cultural conflict can lead to anomie among Chinese adolescents. The data analyzed were collected from a sample of more than 6, 500 middle school students. Structural equation modeling was employed to test the hypothesized relationships. The study found that attachment to traditional Chinese cultural values, especially showing respect to conventional figures/values, reduces anomie among adolescents. In contrast, attraction to WPC and being socially labeled as a big fan of WPC elevate the levels of anomie reported by the students. Reflections on cultural conflict and relevant policy implications are provided in the "Discussions and conclusions" section.